EKSPLORASI PENGGUNAAN MEDIA GAMBAR BERSERI DALAM MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA DINI: Eksplorasi Penggunaan Media Gambar Berseri dalam Meningkatkan Kemampuan Berbicara Anak Usia Dini - Yunitasari, Dwi; Febriany, Ryke Dhea; Na’imah, Ifa jumrotun (jsd: Journal of Society and Development, 2025)
Amid growing concerns about early childhood language delays in the digital era, the use of engaging visual media has become increasingly essential to support oral language development. This study aims to explore the use of sequential picture media in enhancing the speaking abilities of young children at TK Dharma Wanita Hargomulyo Kedewan Bojonegoro. A qualitative research approach was employed, using observations, interviews, and documentation involving a group of children aged 4–5 years. The results indicate that serial picture media effectively stimulate children to speak both individually and in groups. Through storytelling activities based on the provided images, children were able to develop their speaking skills, enrich their vocabulary, and improve sentence structure. In addition, the children showed positive responses to these activities, demonstrated by increased confidence in speaking and improved interaction with peers. The study concludes that serial picture media serve as an effective, enjoyable, and interactive tool for developing young children’s speaking abilities, and contribute by strengthening practical visual-based language learning strategies that can be easily implemented by early childhood educators.